O desenvolvimento da Biotecnologia Industrial nos processos de produção no estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Industrial biotechnology also known as white biotechnology, has been observed as the production of the future. The objective of this research is to analyze the development of industrial biotechnology in the production processes in the State of Amazonas. This is a multi-cases research, with a quali-quantitative approach with exploratory and descriptive approaches. A mapping of the companies and research institutes was made, as to the difficulties faced and the challenges. A bibliographic and exploratory research was carried out in official sites and a questionnaire was applied to local companies. From the data collected, the stage of development and its advances based on this concept were analyzed, as well as the obstacles that interfere in its evolution. The intention was also to identify the legal parameters, the degree of evolution, and comparisons with other states. Its relevance will be not only to expand the body of scientific knowledge on the subject, but also to present the practices of the industrial processes in the State of Amazonas. The results achieved were the mapping of the companies and research institutes that act in conformity with its concepts, as well as the obstacles that were observed. The research projects, in their majority, are developed by the CBA (Center of Biotechnology of Amazonas, which recently changed its name to Center of Bionegocios of Amazonas). A survey was made of activities that are generating products derived from biodiversity that can be understood within this philosophy, exemplifying the coffee of Apuí produced in the city of Apuí-AM, as well as the derivatives of the camu-camu fruit produced in some municipalities of the state. Although the State of Amazonas has industries focused on industrial biotechnology, the mapping employed by Map Biotech verified only 4 companies, one startup and three national companies, both within the city of Manaus. However, several other local entities were observed, which for not having in the description of their CNAE (classification of productive activity with the IRS) the word biotechnology, are left out of surveys, given that each region has its peculiarities, and these organizations that make the mappings should adjust by creating new search methodologies. The results achieved were the construction of a mapping tool, applied to the search for companies and research institutes in the state on websites and platforms that pointed to the existence of 40 companies and 4 research institutes, of which, 36 are in the city of Manaus and 7 in the interior of Amazonas. As for the classification by segment of activity, the results were 11 are from the Food sector, 3 from Biorefinery, 2 from Inputs, 8 from Cosmetics, 5 Environmental, 1 from Bioenergy, 2 from Pharmaceuticals, 7 from Chemicals and 5 from Innovation. As for the use of industrial biotechnology, 34 companies and research institutes are
The development of Industrial Biotechnology in production processes in the state of Amazonas
Keywords: Biotecnologia - Indústria; CIENCIAS BIOLOGICAS: BIOLOGIA GERAL; Biotecnologia Industrial; Industria; Produção; Evolução; Biotecnológica